A novel model to culture cells from giant cell tumor of bone using three‐dimensional (3D) polycaprolactone scaffold - Estrada‐Villaseñor, Eréndira; Valdés‐Flores, Margarita; Meneses‐García, Abelardo; Silva‐Bermudez, Phaedra; Pichardo‐Bahena, Raul; Ostoa‐Saloma, Pedro; Mercado‐Celis, Gabriela; Delgado‐Cedillo, Ernesto D.; Olivos‐Meza, Anell; Landa‐Solís, Carlos (Engineering in life sciences, 2021)
Two‐dimensional (2D) culture of cells from giant cell tumor of bone (GCTB) is affected by loss of the multinucleated giant cells in subsequent passages. Therefore, there is limited time to study GCTB with all its histological components in 2D culture. Here, we explored the possibility of culturing GCTB cells on a polycaprolactone (PCL)‐printed scaffold. We also evaluated the viability of the cultured cells and their adherence to the PCL scaffold at day 14 days using immunofluorescence analysis with calcein, vinculin, and phalloidin. Using the histological technique with hematoxylin and eosin staining, we observed all the histological components of GCTB in this 3D model. Immunohistochemical assays with cathepsin K, p63, and receptor activator of nuclear factor (NF)‐κB ligand (RANKL) yielded positive results in this construct, which allowed us to confirm that the seeded cells maintained the expression of GCTB markers. Based on these findings, we concluded that the PCL scaffold is an efficient model to culture GCTB cells, and the cell viability and adherence to the scaffold can be preserved for up to 14 days. Moreover, this model can also be used in subsequent studies to assess in vitro cell–cell interactions and antineoplastic efficacy of certain agents to establish a treatment against GCTB.